Incidence of hemorrhagic cystitis following unmanipulated peripheral blood stem cell transplantation in acute Leukemia: A retrospective single-center risk factor analysis. Issue 1 (February 2023) - Rostami, Tahereh; Aghabeigi, Sohrab; Kiumarsi, Azadeh; Kasaeian, Amir; Parizi, Mehdi Kardoust; Mirhosseini, Amirhosein; Rostami, Mohammad Reza; Babakhani, Davoud; Tavakoli, Farnaz; Janbabai, Ghasem; Mousavi, Seied Asadollah
Summary: Background: Hemorrhagic cystitis (HC) is an important adverse event experienced after hematopoietic stem cell transplantation (HSCT). Severe HC could lead to significant morbidity, prolonged hospitalization with increased health-care costs, and may cause considerable mortality. Objectives: In order to investigate the influence of different contributing factors other than BK viruria on HC occurrence in a homogenous population, we retrospectively analyzed the potential risk factors. Study design: We conducted a retrospective study among 200 patients (median age 12.4 years, IQR: 7.9–16.1) with acute leukemia who received peripheral blood allogenic HSCT after radiation-free myeloablative conditioning regimen, in pediatric cell therapy department of Research Institute for Oncology, Hematology and Cell Therapy (RIOHCT), Tehran, Iran, between December 2014 and December 2021. Associations between risk factors and outcomes were examined by univariable and multivariable logistic regression models. Results: A total of 46 patients (23%) had developed HC during the study period. The median onset of HC was 29 (IQR: 24–37) days post-transplant, and it persisted for a median of 33 (7–270) days. The incidence of HC in our patients was estimated to be 3 in 1000 cases (95% CI: 2–4). The results of multivariable logistic model shows that the chance of HC in T-cell acute lymphoblastic leukemia (ALL) compared to B-cell All is nearly five times more (OR = 4.88; 95%CI: (1.51–15.78), P = 0.008). The incidence of HC in patients who underwent HSCT from haploidentical donors was significantly higher than full matched donors (P < 0.001). Undergoing transplant from a matched unrelated and haploidentical donor both augment the chance of HC in about six times more than matched related donors (OR = 6.36; 95%CI: (1.58–25.49), P = 0.009 and OR = 5.7; 95%CI: (1.83–17.75), P = 0.003, respectively). In patients who developed HC compared to non-HC group, overall survival was much worse (P < 0.001). Discussion: Most studies have failed to demonstrate any relationship between late-onset HC and the dose of cyclophosphamide. In our study, although the dose of cyclophosphamide was similar in HSCT from MRD and MUD, the hazard of HC incidence was significantly higher in the latter group. This could be accredited to ATG, as in patients in the MRD group who had not received any ATG, the incidence of HC was much lower than the patients who had underwent HSCT from MUD or haploidentical donor group. Conclusions: Patients with T-cell ALL and those who under haploidentical HSCT had the highest incidence of HC. Summary figure Summary figure